NILAI-NILAI PENDIDIKAN AKHLAK DALAM KISAH UWAIS AL-QARNI PERSPEKTIF SHAHIH MUSLIM NOMOR 2542: Values of Moral Education in the Story of Uwais al-Qarni from the Perspective of Sahih Muslim Number 2542 - Atho’illah; Johan Indrus Tofaynuddin (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
The issue of moral education remains a priority. This is especially true when we consider the current decline in the morals of Muslims, such as the disharmony between children and parents. To address this issue, this article aims to examine the values of moral education in the story of Uwais al-Qarni in Sahih Muslim Hadith Number 2542. In Islamic education, the story method has been proven to stimulate individuals to improve their moral character. This article is written using a qualitative approach and literature study. The data sources are Hadith books and other literature relevant to the theme of the article. This article shows that the story of Uwais is not just a classic spiritual narrative, but a reflective mirror that offers profound relevance to contemporary Islamic education. The moral values of Uwais that can be emulated by the younger generation of Muslims include: birrul walidain, patience, gratitude, zuhud, wara', and qana'ah. Persoalan pendidikan akhlak masih menjadi isu yang harus diutamakan. Terlebih jika melihat kemerosotan akhlak umat muslim saat ini, seperti disharmoni anak dan orang tua. Untuk menanggulangi persoalan tersebut, artikel ini bertujuan menelaah nilai-nilai pendidikan akhlak dalam kisah Uwais al-Qarni dalam Hadis Shahih Muslim Nomor 2542. Dalam pendidikan Islam, metode kisah terbukti dapat memberikan stimulasi kepada seseorang untuk meningkatkan kualitas akhlaknya. Artikel ini disusun dengan pendekatan kualitatif dan jenis studi pustaka. Sumber data berupa kitab Hadis dan literatur lain yang relevan dengan tema artikel. Artikel ini menunjukkan bahwa kisah Uwais bukan sekedar narasi spiritual klasik, melainkan sebuah cermin reflektif yang menawarkan relevansi mendalam terhadap pendidikan Islam kontemporer. Nilai-nilai akhlak Uwais yang dapat diteladani oleh generasi muda muslim antara lain: birrul walidain, sabar, syukur, zuhud, wara’ dan qana’ah. Kata Kunci :  Nilai-Nilai Pendidikan; Pendidikan Akhlak; Shahih Muslim; Uwais Al-Qarni.